Pengabdian Kesiapsiagaan Bencana Erupsi Gunung Merapi Terhadap Masyarakat Klakah ,Selo , Boyolali - Fatimah, Fatimah; Paramitha Tedja Trisnaning; Apriani, Ani; Ayu Candra Kurniati (Institut Teknologi Nasional Yogyakarta, 2024)
Community service regarding disaster preparedness is motivated because Mount Merapi is an active volcano that erupts every time and is now on alert level III. The Klakah area is a KRB III area, so the community needs to get socialization and knowledge about volcanic activity and preparedness for the Merapi eruption disaster. This community service was carried out in 2023 in Klakah, Selo, Boyolali with participants from the village government and the Klakah disaster response community. This community service starts from situation analysis, socialization, analysis by distributing questionnaires, and suggestions for the village government. The results of this community service show that community participation is quite high in participating in community service activities and they also care about disaster-related matters. The community already knows the vulnerability of the area where they live. The community further improves relations with the relevant government when a disaster occurs, even though the measured level of resilience is 50%.